Didymoceras puebloense, a new species of heteromorph ammonite from the Upper Campanian of Colorado and Wyoming - Cobban, W; Kennedy, W; Scott, G (1997)
Didymoceras puebloense nov. sp. is described from the upper Campanian zones of Didymoceras nebrascense and Didymoceras stevensoni in Pueblo and Pitkin Counties, Colorado, and Weston County, Wyoming in the United States Western Interior. The species is characterized by a middle helical growth stage in which the successive whorls are widely separated followed by a terminal pendant U-shaped sector of the adult body chamber. Ornament is of distant, narrow bituberculate ribs usually separated by a nontuberculate rib. Widely separated poorly-defined constrictions with associated collar ribs are occasionally present. The style of coiling in middle and later growth resembles that of those growth stages in upper Campanian Didymoceras, whereas the ornament recalls that of middle Campanian representatives of the genus in the Western Interior.